Hydration status during commercial saturation diving measured by bioimpedance and urine specific gravity - Wekre, Stian Lande; Landsverk, Halvor Dagssøn; Lautridou, Jacky; Hjelde, Astrid; Imbert, Jean Pierre; Balestra, Costantino; Eftedal, Ingrid (Frontiers in Physiology, 2022)
Excessive fluid loss triggered by hyperbaric pressure, water immersion and hot water suits causes saturation divers to be at risk of dehydration. Dehydration is associated with reductions in mental and physical performance, resulting in less effective work and an increased risk of work-related accidents. In this study we examined the hydration status of 11 male divers over 19 days of a commercial saturation diving campaign to a working depth of 74 m, using two non-invasive methods: Bioelectrical impedance analysis (BIA) and urine specific gravity (USG). Measurements were made daily before and after bell runs, and the BIA data was used to calculated total body water (TBW). We found that BIA and USG were weakly negatively correlated, probably reflecting differences in what they measure. TBW was significantly increased after bell runs for all divers, but more so for bellmen than for in-water divers. There were no progressing changes in TBW over the 19-day study period, indicating that the divers’ routines were sufficient for maintaining their hydration levels on short and long term.